APPLICATION OF THE SNAKE METHOD TO IMPROVE THE STUDENT RESULTS OF CLASS IV STUDENTS OF SD NEGERI NO. 101731 KAMPUNG LALANG - Dewi Anzelina (JURNAL HANDAYANI PGSD FIP UNIMED, 2020)
Abstract:This study aims to determine the i mprovement of science learning outcomes by applying the debt (snakes and ladders) method to class IV students of SD Negeri 101731 Kampung Lalang in understanding the material changes in the appearance of the earth and celestial bodies .This type of research is classroom action research with a total of 33 research subjects from grade IV students at SD Negeri 101731 Kampung Lalang , where activities are carried out while learning science takes place. To obtain data used in this study the authors conducted tests and observations. The data analysis technique in this study is a qualitative description by describing the percentage used. Based on the results of the study in the first cycle of 33 students who have been studying about p okok discussion of changes in the earth's surface appearance and the heavenly bodies was found that students who received grades < 70 or did not complete as many as 17 students ( 51.52 %) and students who achieve ni lai ≥ 70 or as many as 1 6 students ( 48.48 %). The average acquisition result or learning value is 68.03. Classical completeness is 57.58%. This proves that the value of student learning outcomes in the implementation of the first cycle does not yet have a success rate of learning because it is still below 80.00%. Based on the acquisition of learning outcomes in the first cycle still has not reached completion so that the second cycle is carried out. The results of the data in the second cycle there were 31 students (93.94%) completeness and did not experience completeness of 2 people (6.06%). Acquisition of classical completeness of 93.94%, this proves that classical learning outcomes in the second cycle has reached completeness because it has reached 80.00% with the acquisition of an average value of 88.79. Thus it can be concluded that an increase in student learning outcomes after learning is done by using the snake ladder method in science lessons the subject of changes in the appearance of the surface of the earth and celestial bodies in class IV SD Negeri N o . 101731 Kampung Lalang for the Academic Year 2017/2018 .Keywords : Ladder Snake Mhod, Learning OutcomesAbstrak : Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar IPA dengan menerapkan metode utang (ular tangga) pada siswa kelas IV SD Negeri No.101731 Kampung Lalang dalam memahami materi perubahan kenampakan bumi dan benda langit. Jenis penelitian ini adalah penelitian tindakan kelas dengan jumlah subjek penelitian sebanyak 33 orang siswa yang berasal dari siswa kelas IV SD Negeri No.101731 Kampung Lalang, dimana kegiatan dilakukan saat pembelajaran IPA berlangsung. Untuk memperoleh data yang digunakan dalam penelitian ini penulis melakukan test dan observasi. Adapun teknik analisis data dalam penelitian ini adalah deskripsi kualitatif dengan menguraikan persentase yang digunakan. Berdasarkan hasil pelaksanaan pembelajaran pada siklus I dari 33 siswa yang telah mempelajari tentang pokok bahasan perubahan kenampakan permukaan bumi dan benda langit diperoleh bahwa siswa yang memperoleh nilai < 70 atau tidak tuntas sebanyak 17 siswa (51,52%) dan siswa yang mencapai nilai ≥ 70 atau tuntas sebanyak 16 siswa (48,48%). Rata-rata perolehan hasil atau nilai belajar sebesar 68,03. Tingkat ketuntasan klasikal mencapai 57,58%. Hal ini membuktikan bahwa nilai hasil belajar siswa pada pelaksanaan siklus I belum memiliki tingkat keberhasilan belajar karena masih di bawah 80,00%. Berdasarkan perolehan hasil belajar pada siklus I masih belum mencapai ketuntasan sehingga dilaksanakan siklus II. Hasil data pada siklus II terdapat 31 siswa (93,94%) ketuntasan dan tidak mengalami ketuntasan 2 orang (6,06%). Perolehan ketuntasan klasikal sebesar 93,94% hal ini membuktikan bahwa hasil belajar secara klasikal pada siklus II telah mencapai ketuntasan karena telah mencapai 80,00% dengan perolehan nilai rata-rata sebesar 88,79. Dengan demikian dapat disimpulkan bahwa terjadi peningkatan hasil belajar siswa setelah dilakukan pembelajaran dengan menggunakan metode ular tangga pada pelajaran IPA pokok bahasan perubahan kenampakan permukaan bumi dan benda langit di kelas IV SD Negeri No. 101731 Kampung Lalang Tahun Pembelajaran 2017/2018.Kata Kunci : Metode Ular Tangga, Hasil Belajar